Different patients, different preferences: a multicenter assessment of patients' personality traits and anxiety in shared decision making - Alpers, Georg W.; Köther, Anja Kristina; Büdenbender, Björn; Grüne, Britta; Holbach, Sonja; Huber, Johannes; Landenberg, Nicolas von; Lenk, Julia; Martini, Thomas; Michel, Maurice Stephan; Kriegmair, Maximilian (Cancer medicine, 2022)
Patient-centered care and shared decision making (SDM) are generally recognized as the gold standard for medical consultations, especially for preference-sensitive decisions. However, little is known about psychological patient characteristics that influence patient-reported preferences. We set out to explore the role of personality and anxiety for a preference-sensitive decision in bladder cancer patients (choice of urinary diversion, UD) and to determine if anxiety predicts patients' participation preferences. Methods: We recruited a sample of bladder cancer patients (N = 180, primarily male, retired) who awaited a medical consultation on radical cystectomy and their choice of UD. We asked patients to fill in a set of self-report questionnaires before this consultation, including measures of treatment preference, personality (BFI-10), anxiety (STAI), and participation preference (API and API-Uro), as well as sociodemographic characteristics. Results: Most patients (79%) indicated a clear preference for one of the treatment options (44% continent UD, 34% incontinent UD). Patients who reported more conscientiousness were more likely to prefer more complex methods (continent UD). The majority (62%) preferred to delegate decision making to healthcare professionals. A substantial number of patients reported elevated anxiety (32%), and more anxiety was predictive of higher participation preference, specifically for uro-oncological decisions (β = 0.207, p < 0.01). Conclusions: Our findings provide insight into the role of psychological patient characteristics for SDM. Aspects of personality such as conscientiousness influence treatment preferences. Anxiety contributes to patients' motivation to be involved in pertinent decisions. Thus, personality and negative affect should be considered to improve SDM.